Investigate The Relationship Between Cost Management Strategy, Organization Size, Growth Options and The Performance Of Companies In Tehran Stock Exchange - Sedaghati, Moslem; Noodezh, Hamid Ravanpak; Amiri, Ali (Ciência e Natura, 2015)
This study aimed to investigate the relationship between cost management strategy, organization size and growth Options on the performance of the company. In this regard, the financial statements of 76 companies listed in Tehran Stock Exchange for the years 2009 to 2013 were analyzed. In this study, cost management strategy (the ratio of capital expenditure to sales, sales of the book value of fixed assets) and size (natural logarithm of total assets) and growth Options (market value of assets to book value of assets) as a variable. independent, and firm performance (return on assets, sales growth) was used as the dependent variable, so that the relationship between strategy, size, growth Options and firm performance during a 5-year period studied. The method used for data collection, library and field. To test the hypotheses of the model Autoregressive conditional heteroscedasticity (ARCH) and generalized regression model, the conditional heteroscedasticity (GARCH) were analyzed using the software Eviews8. And significance was determined using a Z score and likelihood ratio. The criteria for the variable sales strategy to sell the book value of fixed assets and the capital expenditure of a significant and positive relationship with sales growth. In the capital, Tehran Stock Exchange Market participants are recommended to consider it as the time-varying volatility and time efficiencies associated with corporate assets can be public relations strategy, cost management and growth Options of the company described. Also associated with the company’s sales growth can be described by the relationship between the size and cost management strategy